Improving Students’ Speaking Skills by Using Duolingo Application - Yelsa Dearestiani; Abdul Rohman; Widi Syahtia Pane (Inquest Journal, 2023)
Background:This research aimed to find out the Improving Students’ Speaking Skills by Using Duolingo Application. Thesubject of this research was a class which consisted of 31 students at eight grade of SMP Negeri 35 Samarinda2022 Academic year. The research was conducted by using Classroom Action Research (CAR) and the techniqueof analyzing the data of this research was using quantitative data. The quantitative data were taken from the testsuch as: Pre-test and Post-test to find the mean score of students speaking. It showed that the improving of studentsspeaking skills through Duolingo application could improve students speaking skills and could give an effect onstudents speaking fluency. The students got more enthusiastic, active and interested in learning English language.So, it can be concluded that the improving of students’ speaking skills through Duolingo application was effectiveto improve their speaking fluency, pronoun, grammar, and comprehension. Methodology:This research is design to look at the problem in a class about how to fix the problem and improve StudentsEnglish skills. Findings:The researcher did the research and got the complete data from all the research instruments. Conclusion:Duolingo improves students' speaking skills. According to research, using Duolingo to practice speakingimproves speaking skills. The study found that the mean score increased in every cycle. Originality:This research aimed to find out the Improving Students’ Speaking Skills by Using Duolingo Application. ThisResearch design is to look at the problem in a class about to fix the speaking skills and the researcher did theresearch and got the complete data. From this conclusion Duolingo Application is works to help the teacher teachthe students in a class especially on their speaking ability.